Use of organic amendment for management of fusarium wilt of gladiolus - Yasmin, L; Ali, MA (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during 2009-2011 following RCB design with four replications. Eight soil amendments such as Poultry refuse (5 t ha-1), Mustard oil cake (600 kg ha-1), Sesbania rostrata (5 t ha-1), Municipal waste compost (5t ha-1), BARI Trico- compost (2t ha-1), Leachate (200 ml m-2) were evaluated against Fusarium wilt of gladiolus caused by Fusarium oxysporum f. sp. gladioli under field condition. Poultry refuse was very effective in inhibiting the disease resulting maximum germination (99.98%), spike length (73.90 cm), rachis length (43.70 cm), florets spike-1 (12.63), flower sticks plot-1 (38.75) and corm plot-1 (60.23) and cormel yield ha-1 (2.51 t). Mustard oil cake, BARI Trico-compost and Sesbania rostrata compost were also effective in inhibiting the disease and resulting better spike length, rachis length, florets spike-1, flower sticks plot-1 and corm plot-1 and cormel yield. Bangladesh J. Agril. Res. 41(4): 675-684, December 2016